Neurogenic-dependent changes in hippocampal circuitry underlie the procognitive effect of exercise in aging mice - Xiaoqing Alice Zhou (Elsevier, 2021)
Summary: We have shown that the improvement in hippocampal-based learning in aged mice following physical exercise observed is dependent on neurogenesis in the dentate gyrus (DG) and is regulated by changes in growth hormone levels. The changes in neurocircuitry, however, which may underlie this improvement, remain unclear. Using in vivo multimodal magnetic resonance imaging to track changes in aged mice exposed to exercise, we show the improved spatial learning is due to enhanced DG connectivity, particularly the strengthening of the DG-Cornu Ammonis 3 and the DG-medial entorhinal cortex connections in the dorsal hippocampus. Moreover, we provide evidence that these changes in circuitry are dependent on neurogenesis since they were abrogated by ablation of newborn neurons following exercise. These findings identify the specific changes in hippocampal circuitry that underlie the cognitive improvements resulting from physical activity and show that they are dependent on the activation of neurogenesis in aged animals.